If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(3b + 4) + (10b + -7) = 0 Reorder the terms: -1(4 + 3b) + (10b + -7) = 0 (4 * -1 + 3b * -1) + (10b + -7) = 0 (-4 + -3b) + (10b + -7) = 0 Reorder the terms: -4 + -3b + (-7 + 10b) = 0 Remove parenthesis around (-7 + 10b) -4 + -3b + -7 + 10b = 0 Reorder the terms: -4 + -7 + -3b + 10b = 0 Combine like terms: -4 + -7 = -11 -11 + -3b + 10b = 0 Combine like terms: -3b + 10b = 7b -11 + 7b = 0 Solving -11 + 7b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + 7b = 0 + 11 Combine like terms: -11 + 11 = 0 0 + 7b = 0 + 11 7b = 0 + 11 Combine like terms: 0 + 11 = 11 7b = 11 Divide each side by '7'. b = 1.571428571 Simplifying b = 1.571428571
| -3(2s-3)-9=-3(6s+6)-5 | | (3/17)x=15 | | 15x=53000+2.70x | | t+27=13 | | 21X^2-20X+4= | | 6w-5/8=7/8 | | X+2+x+5=7 | | 2x-2=5x-15 | | 14X^2-65X+9= | | (x+10)+(4x-16)+x=642 | | 0.7w-0.6w+0.4w=2 | | 228-84= | | 0.7(6x+12)=1.8-(x+2) | | 25(-2x+5)=.13x+3 | | 9(y^6)^4/(6y) | | 2/5x-5/25x=5 | | (9x+10)+(4x-16)+x=642 | | 4(2x-11)/13=-(x+5) | | (22b-6)-7(3b+3)=-6 | | 8/3x5/2 | | 11(x-1)-6-(x+7)= | | 7x+5x+4+9=6x+4+5x | | 90t+90t=360 | | 3x-37=x/6+14 | | -(8y+1)-(-7y-3)=1 | | 950t+800t=4375 | | x+x+2+x+4=393 | | 11-x=-5 | | 56-g=12 | | 56-6=12 | | 2.6x-2.6-5.2x=-3.6x-1.1 | | 17-t=98 |